Effect of Proper Management of Cocoa Plants on the Occurrence of Swollen Shoot Disease in Kipiri - Côte d'Ivoire - Oro, F.Z.; Lallié, H.D.; N’Guessan, C.A.; Kouadio, J.; Diby, L.; Kouamé, C.; Diallo, H.A. (Sciencedomain International, 2020)
This study aimed to evaluate the relationship between plot maintenance level and the prevalence of Cocoa swollen shoot disease in Kipiri (Department of Soubré) in Côte d'Ivoire. Indeed, the strong pressure of Swollen shoot disease in this department causes enormous damage in cocoa plots.The study design is a prospective survey in peasant cocoa plots between 2014 and 2016. The data were collected using the Land Degradation Surface Framework (LDSF). The LDSF device is a sentinel site of 10 Km × 10 Km. The site is divided into 16 Clusters of 2.5 Km × 2.5 Km with 10 plots by cluster. In the case of our study, surveys were carried out on 108 plots carrying cocoa trees within a radius of 50 m around each test plot. The data collected included areas of Cocoa Swollen Shoot Virus (CSSV) outbreaks, the cocoa plot maintenance level and CSSV status like ‘Absence’ or ‘Presence’ in plots observed. CSSV prevalence was deduced from CSSV outbreaks areas of each sampling plot, allowing realization of disease map. The relationship between the level of plot maintenance and the prevalence of CSSV was assessed by using the analysis of variance test (Anova-one-way). The results of Swollen shoot disease’s distribution showed that the Kipiri site had a CSSV prevalence around 50%.These results demonstrated that plots maintenance level has a strong influence on the prevalence of Swollen shoot disease (p =0.00 < 0.05). At the end of this study, it appears that plots maintenance level is a key factor in the rapid spread of the Swollen shoot epidemic in Kipiri site. Cocoa producers would therefore be recommended to regularly maintain their plantations by eliminating the reservoirs of Cocoa Swollen Shoot Virus.